Exploring the molecular differentiation of sex chromosomes in Anastrepha fraterculus sp. 1 using comparative genomic hybridization (CGH) - Giardini, Maria Cecilia; Milla, Fabian Horacio; Conte, Claudia Alejandra; Lanzavecchia, Silvia Beatriz; Nieves, Mariela (Springer, 2025)
Background: The South American fruit fly Anastrepha fraterculus sp. 1 belongs to a cryptic species complex with only a single morphotype present in Argentina, which possess polymorphisms in the sex chromosomes, identified by two X (X1, X2) and two Y (Y5, Y6) variants. Our aim was to explore the molecular composition of the sex chromosomes identified in the laboratory strain Af-Y-short due to it possesses the most frequent sex chromosomes variants, and the smallest Y chromosome found in wild populations and laboratory colonies of A. fraterculus sp. 1. Methods and results: Whole Comparative Genomic Hybridization (W-CGH) was applied to the Af-Y-short laboratory strain to identify potential differences in the size and composition of highly repetitive DNA blocks between individuals, morphs or sexes. Our results showed that the X1 and X2 share complete homology in euchromatic regions, also sharing similar sequences with the Y5 chromosome in the centromeric region. Females X1X1 and X1X2 exhibited repetitive DNA in telomeric regions which contributed to their morphological differentiation, while the Y chromosome evidenced the accumulation of specific and differential repetitive sequences. In contrast, autosomes showed balanced signal with no sex-chromosome-specific sequence accumulation. Conclusions: Our findings highlight the role of repetitive DNA in the differentiation and evolution of sex chromosomes in A. fraterculus sp. 1, shedding new light on the origin and diversification of Anastrepha species in South America and providing valuable cytogenetic insights for future research.